Long‐term Preconditioning with Erythropoietin Reduces Ischemia‐Induced Skin Necrosis. (November 2013) - Rezaeian, Farid; Wettstein, Reto; Scheuer, Claudia; Schenck, Thilo L.; Egaña, Jose T.; Machens, Hans‐Günther; Menger, Michael D.; Harder, Yves
Abstract: Objective: Recent findings have attested to EPO tissue‐protective effects in ischemically challenged tissues. Therefore, the study aimed at elaborating the effect of systemic pre‐ and postconditioning using EPO in a mouse model of persistent ischemia of the skin. Methods: Three groups of nine C57Bl/6‐mice each were analyzed. The experimental groups consisted of untreated controls, EPO preconditioning, and EPO postconditioning (500 IU EPO/kg bw/day for 10 days). Critically perfused skin flaps undergoing necrosis, if kept untreated, were mounted into dorsal skinfold chambers. Intravital epi‐fluorescence microscopy was performed for 10 days to assess tissue necrosis, microcirculation, inflammation, and angiogenesis. Protein expression analysis of eNOS was performed. Hematocrit analyses were carried out separately in eight animals. Results: Only EPO preconditioning was able to significantly reduce necrosis, when compared with controls. This correlated with a significantly increased CD in the critically perfused tissue. Administration of EPO only slightly increased eNOS expression at day 10, when compared with controls. EPO induced angiogenesis and increased hematocrit. Finally, EPO significantly reduced leukocytic inflammation in arterioles in all EPO receiving mice. Conclusions: EPO preconditioning effectively reduces skin necrosis predominantly by capillary maintenance and reperfusion, as well as improved tissue regeneration. Thus, EPO preconditioning might represent a promising, non‐invasive approach to reduce complications in ischemically challenged skin.